Lineage-specific differentiation of osteogenic progenitors from pluripotent stem cells reveals the FGF1-RUNX2 association in neural crest-derived osteoprogenitors. (9th June 2020) - Kidwai, Fahad; Mui, Byron W. H.; Arora, Deepika; Iqbal, Kulsum; Hockaday, Madison; Castro Diaz, Luis Fernandez; Cherman, Natasha; Martin, Daniel; Myneni, Vamsee D.; Ahmad, Moaz; Futrega, Katarzyna; Ali, Sania; et al.
Abstract: Human pluripotent stem cells (hPSCs) can provide a platform to model bone organogenesis and disease. To reflect the developmental process of the human skeleton, hPSC differentiation methods should include osteogenic progenitors (OPs) arising from three distinct embryonic lineages: the paraxial mesoderm, lateral plate mesoderm, and neural crest. Although OP differentiation protocols have been developed, the lineage from which they are derived, as well as characterization of their genetic and molecular differences, has not been well reported. Therefore, to generate lineage-specific OPs from human embryonic stem cells and human induced pluripotent stem cells, we employed stepwise differentiation of paraxial mesoderm-like cells, lateral plate mesoderm-like cells, and neural crest-like cells toward their respective OP subpopulation. Successful differentiation, confirmed through gene expression and in vivo assays, permitted the identification of transcriptomic signatures of all three cell populations. We also report, for the first time, high FGF1 levels in neural crest-derived OPs—a notable finding given the critical role of fibroblast growth factors (FGFs) in osteogenesis and mineral homeostasis. Our results indicate that FGF1 influences RUNX2 levels, with concomitant changes in ERK1/2 signaling. Overall, our study further validates hPSCs' power to model bone development and disease and reveals new, potentially important pathways influencing these processes. : Abstract : Human pluripotent stem cells were stepwise differentiated toward paraxial mesoderm-, lateral plate mesoderm-, and neural crest-derived osteogenic progenitors (OPs). Transcriptomic signatures of these three cell subpopulations were identified, with a new finding of high FGF1 levels and its association with RUNX2 in neural crest-derived OPs.